No Evidence for an Auditory Attentional Blink for Voices Regardless of Musical Expertise - Akça, Merve; Laeng, Bruno; Godøy, Rolf Inge (Frontiers in Psychology, 2020)
Background. Attending to goal-relevant information can leave us metaphorically ‘blind’ or ‘deaf’ to the next relevant information while searching among distracters. This temporal cost lasting for about a half a second on the human selective attention has been long explored using the attentional blink paradigm. Although there is evidence that certain visual stimuli relating to one’s area of expertise can be less susceptible to attentional blink effects, it remains unexplored whether the dynamics of temporal selective attention vary with expertise and objects types in the auditory modality. Methods. Using the auditory version of the attentional blink paradigm, the present study investigates whether certain auditory objects relating to musical and perceptual expertise could have an impact on the transient costs of selective attention. In this study, expert cellists and novice participants were asked to first identify a target sound, and then to detect instrumental timbres of cello or organ, or human voice as a second target in a rapid auditory stream. Results. The results showed moderate evidence against the attentional blink effect for voices independent of participants’ musical expertise. Experts outperformed novices in their overall accuracy levels of target identification and detection, reflecting a clear benefit of musical expertise. Importanly, the musicianship advantage disappeared when the human voices served as the second target in the stream. Discussion. The results are discussed in terms of stimulus salience, the advantage of voice processing, as well as perceptual and musical expertise in relation to attention and working memory performances.